The role of the economic crisis on occupational stress and well being - Perrewe, Pamela L.; Halbesleben, Jonathon R. B.; Rosen, Christopher C. (Emerald, 2012)
The recent economic recession has changed the nature of employment. Workers experience an increasingly uncertain future and many have been forced to search for jobs in a highly competitive market. In this volume, we call upon the fields leading researchers to examine how economic conditions relate to occupational stress and well being.
Keywords: Job stress -- Economic aspects.; Global Financial Crisis, 2008-2009 -- Social aspects.; elektronické knihy; electronic books